1992
DOI: 10.1080/15287399209531648
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and toxicokinetics of carbaryl in chickens and rats: A comparative study

Abstract: Carbaryl, a carbamate insecticide, exerts its toxic effect in animals by inhibiting the activity of neural acetylcholinesterase. Differences in sensitivity of this enzyme to inhibition were studied after intraperitoneal administration to chickens and rats. A dose of 900 mg/kg to chickens and 70 mg/kg to rats caused equivalent inhibition of brain cholinesterase activities (57% +/- 6 and 47% +/- 4, respectively) 60 min after administration, which was the time of maximal cholinergic signs. Signs of toxicity (sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Previous studies demonstrated that AChE activity in the rats was significantly inhibited by chlorpyrifos but no activity inhibited by carbaryl after exposure to these pesticides separately (Ehrich et al,; Sachana et al,), which was similar to the results observed in our current study. The inhibition of AChE in the rats treated with middle‐ and high‐dose of the mixture of chlorpyrifos and carbaryl was similar to that induced by chlorpyrifos alone and no AChE activity inhibition by carbaryl alone was found.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that AChE activity in the rats was significantly inhibited by chlorpyrifos but no activity inhibited by carbaryl after exposure to these pesticides separately (Ehrich et al,; Sachana et al,), which was similar to the results observed in our current study. The inhibition of AChE in the rats treated with middle‐ and high‐dose of the mixture of chlorpyrifos and carbaryl was similar to that induced by chlorpyrifos alone and no AChE activity inhibition by carbaryl alone was found.…”
Section: Discussionsupporting
confidence: 92%
“…The phosphorylation reaction is responsible for the inhibition of AChE, which causes neurotoxicity. An inhibition of brain AChE similar to that in the present study was reported in rats treated with MCP (Janardhan and Sisodia, 1990), carbaryl (Ehrich et al, 1992), and permethrin (Bandyopadhyay, 1982). It has been reported that diplodiatoxin causes mycotoxic peripheral myelinopathy and hepatitis in monkeys (Fincham et al, 1991).…”
Section: Discussionsupporting
confidence: 88%
“…carboxylesterases produced by carbaryl, carbofuran, methomyl, oxamyl, and propoxur (e.g., Barata et al, 2004;Costa and Murphy, 1983;Ehrich et al, 1992;Fossi et al, 1992;Gupta and Dettbarn, 1993;Kadel, 1989, 1990;Parker and Goldstein, 2000). This binding is biologically significant in that coadministration of carboxylesterase inhibitors potentiates the toxicity of carbofuran, oxamyl, and propoxur (Costa and Murphy, 1983;Gupta and Dettbarn, 1993;Kadel, 1989, 1990;Parker and Goldstein, 2000).…”
Section: Neurotoxicity Of Carbamate Mixturesmentioning
confidence: 99%